Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw dan STAD terhadap Kemampuan Membaca Pemahaman Siswa Kelas V SD - Arif Praditya; Qurrotu Inayatil Maula (Mataram University, 2026)
Reading comprehension ability is one of the essential skills that elementary school students must master. However, students still experience difficulties in understanding implicit information and evaluating the content of texts, indicating the need for a more effective learning model. This study aimed to determine the difference in the effects of the Jigsaw and STAD cooperative learning models on the reading comprehension ability of fifth-grade students at UPTD SDN Banyuajuh 3. This research employed a quantitative approach using a quasi-experimental design. The study was conducted at UPTD SDN Banyuajuh 3. The sample was selected using the cluster sampling technique. The participants consisted of Class V-B as the experimental group and Class V-A as the control group. The research instruments included an essay test as the test instrument and an observation sheet as the non-test instrument. Data were analyzed using the Shapiro-Wilk test to examine data normality, the homogeneity of variance test to examine data homogeneity, and the Independent Sample t-test to test the research hypothesis. The results showed that the significance value (2-tailed) was 0.030 (< 0.05), indicating that H₀ was rejected and Hₐ was accepted. Therefore, there was a significant difference in the effect of the Jigsaw and STAD cooperative learning models on the reading comprehension ability of fifth-grade students at UPTD SDN Banyuajuh 3.